Sex-specific associations of blood lead and cadmium levels with sarcopenia in US adults - Yan Chen; Ting Dai; Jing Gao; Xiaodong Feng (Scientific Reports)
Abstract Sex-specific associations of blood lead and blood cadmium levels with sarcopenia in US adults remains unclear. This study aimed to investigate these relationships using data from the National Health and Nutrition Examination Survey (NHANES) 2011–2018. A total of 7,000 adults (3,456 men and 3,544 women) with complete data of blood Pb, Cd, and covariates, and complete Dual-Energy X-ray Absorptiometry (DXA) data for sarcopenia assessment were included, and sarcopenia was diagnosed based on the sarcopenia index (SI). Survey-weighted logistic regression models adjusted for sociodemographic, lifestyle, and health-related covariates, including age, sex, race, educational level, marital status, poverty-to-income ratio (PIR), drinking status, waist circumference, and BMI, were used to estimate odds ratios (ORs). Blood Pb level showed a positive association with sarcopenia risk in both sexes, especially in males (Q4 vs. Q1: Weighted OR = 2.53, 95% CI: 1.17–5.47; P = 0.02), while blood Cd exhibited a positive association with sarcopenia risk only in females (Q4 vs. Q1: Weighted OR = 5.08, 95% CI: 2.46–10.46; P < 0.01). Sex-stratified RCS analysis suggested nonlinear associations of Pb (P–nonlinear < 0.01) and Cd (P–nonlinear < 0.01) with sarcopenia risk, with males demonstrating steeper risk increments at higher Pb levels and females exhibiting steeper risk increments at higher Cd levels. These findings highlight sex-specific disparities in metal toxicity, suggesting that Pb and Cd exposure may differentially contribute to sarcopenia risk. Potential mechanisms could include via hormonal and body composition pathways.